Identification and functional analysis of αB-crystallins in Pteromalus puparum - Lao, Shuxing; Xiong, Shijiao; Fang, Qi; Ye, Gongyin (Frontiers in Physiology, 2023)
Heat shock proteins, including αB-crystallins (CRYAB), are pivotal in cellular defense mechanisms and stress response. This study presents a comprehensive investigation of heat shock proteins (HSPs), with a specific focus on the CRYAB family, within the genome of Pteromalus puparum. The analysis encompasses the identification of these proteins, exploration of their phylogenetic relationships, examination of conserved domains, and evaluation of their response to high temperature conditions. A total of 46 HSPs were identified in the P. puparum genome, and the differential expression of mRNA at 35°C and 25°C drew attention to five genes belonging to the CRYAB family, namely PpCRYAB-1 to PpCRYAB-5. The conservation level of CRYAB family genes across different species was observed to be relatively modest. Through genome-wide screening of 22 species representing six insect orders, a total of 235 CRYAB proteins were identified, with P. puparum harboring eight CRYAB proteins, indicative of a moderate abundance compared to other species. Intriguingly, evolutionary analysis highlighted PpCRYAB-4 with potentially intricate differentiation in comparison to other members of the CRYAB family. Furthermore, RNA interference (RNAi) results demonstrated significant regulatory effects on adult lifespan under heat stress at 35°C for PpCRYAB-4 and PpCRYAB-5. These findings lay a groundwork for future investigations into stress resistance mechanisms in parasitic wasps, providing fresh insights for the study of insect resilience amidst the backdrop of global climate change.